2008
DOI: 10.1148/rg.287085095
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyomas beyond the Uterus: Unusual Locations, Rare Manifestations

Abstract: Uterine leiomyomas affect 20%-30% of women older than 35 years. Extrauterine leiomyomas are rarer, and they present a greater diagnostic challenge: These histologically benign tumors, which originate from smooth muscle cells, usually arise in the genitourinary tract (in the vulva, ovaries, urethra, and urinary bladder) but may arise in nearly any anatomic site. In addition, unusual growth patterns may be seen, including benign metastasizing leiomyoma, disseminated peritoneal leiomyomatosis, intravenous leiomyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
384
1
25

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(424 citation statements)
references
References 63 publications
1
384
1
25
Order By: Relevance
“…Microscopically, the round nodules consist of mature fusiform smooth muscle cells and these cells are arranged in interdigitating fascicles [9,10]. The nodules are lack of mitotic figures or the mitotic index (MI) is less than 3/10 high power field (HPF).…”
Section: Discussionmentioning
confidence: 99%
“…Microscopically, the round nodules consist of mature fusiform smooth muscle cells and these cells are arranged in interdigitating fascicles [9,10]. The nodules are lack of mitotic figures or the mitotic index (MI) is less than 3/10 high power field (HPF).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, unusual growth patterns may be seen, including benign metastasizing leiomyoma, disseminated peritoneal leiomyomatosis, intravenous leiomyomatosis, parasitic leiomyoma, and retroperitoneal growth. 2,6 More than 40% of patients affected by this retroperitoneal condition have a concurrent uterine leiomyoma or a remote history of hysterectomy for treatment of a uterine leiomyoma. 5 However, some extrauterine leiomyomas may mimic malignancies, and serious diagnostic errors may result.…”
Section: Discussionmentioning
confidence: 99%
“…Retroperitoneal leiomyomas, defined as those located posterior to parietal peritoneum, are a very rare occurrence. [1][2][3][4] As of 2007 (1941-2007), only 37 retroperitoneal leiomyomas have been reported in the literature with comprehensive information. There is a need for further research on this condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that >50% of intravenous LG-ESS cases exhibited ICE (8). In such cases, the extent of the tumor should be determined using modalities such as MRI and ultrasonography, in addition to CT. MRI provides good soft tissue resolution and helps to distinguish an intravascular tumor from a non-tumor thrombus (16)(17)(18), whereas Doppler ultrasonography is also useful (16). Transthoracic ultrasonography of the IVC and heart would normally be performed.…”
Section: Discussionmentioning
confidence: 99%